Diophantine Triples Involving Octagonal Numbers - R. Radha; G. Janaki; M. Madhumika (Explorations in Diophantine Equations, 2023)
We search for three different polynomials with integer that produce a perfect square when any two numbers from the set are added together and then their sum is subtracted by an integer other than zero.